182k views
1 vote
Is the expression 2f + 4f + 2 – 3 equivalent to 6f – 1?

6f – 1 evaluated at f = 9 is 53.

2f + 4f + 2 – 3 evaluated at f = 9 is also 53.



6f – 1 evaluated at f = 3 is 17.

What is 2f + 4f + 2 – 3 evaluated at f = 3?

iv been stuck for 10 min now

2 Answers

1 vote
6f-1 and 2f+ 4f +2-3 are equal. 2f +4f+2-3 is 17 at f=3 because

(2•3)+(4•3)+(2-3) =

(6+12)+(-1) =

(18)+(-1)=

17
Plug in what f equals for f in the equation and evaluate
I hope this helps.
Is the expression 2f + 4f + 2 – 3 equivalent to 6f – 1? 6f – 1 evaluated at f = 9 is-example-1
User Feuda
by
4.8k points
1 vote

Answer:

Yes it is equivalent.

Explanation:

In this case the only thing that you have to do to know if the two expressions are equivalent are put them on opposite sides of the equation like this:

6f-1= 2f+4f+2-3

When you simplify this you´ll end up with the next equation:

6f-1= 6f -1

In this case you can see that both expressions are equivalent because they are the same once you put them on opposite sides of the equation.

User ViviG
by
5.4k points